The Sermon on the mount and spiritual exercises: the making of the Matthean self - Branch-Trevathan, George (Novum Testamentum / Supplements, 2020)
"What, in Matthew's view, should a human being become and how does one attain that ideal? In The Sermon on the Mount and Spiritual Exercises: The Making of the Matthean Self, George Branch-Trevathan presents a new account of Matthew's ethics and argues that the evangelist presents the Sermon on the Mount as functioning like many other ancient sayings collections, that is, as facilitating transformative work on oneself, or "spiritual exercises," that enable one to realize the evangelist's ideals. The conclusion suggests some implications for our understanding of ethical formation in antiquity and the study of ethics more generally. This will be an essential volume for scholars studying the Gospel of Matthew, early Christian ethics, the relationships between early Christian and ancient philosophical writings, or ethical formation in antiquity"--